PERAN PENYULUH PERTANIAN LAPANGAN DALAM PENGEMBANGAN GABUNGAN KELOMPOK TANI DI DESA WONOSARI KECAMATAN SEPAKU KABUPATEN PENAJAM PASER UTARA (The Role of Field Agriculture Instructor in the Development of Farmers Groups Association in Wonosari Village Sepaku Subdistrict Penajam Paser Utara District) - ERICA FATMITA RAMADANI; DINA LESMANA; MIDIANSYAH EFFENDI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2020)
The purposes of this research were to know the role of Field Agriculture Instructor (FAI) in the development of Farmers Groups Association (FGA), the development of FGA, and the relationship between the role of FAI and the development of FGA. This research was conducted during three months from August to October 2015. The role of FAI in the development of FGA was analyzed by using Chi Square. The relationship between the role of FAI and the development of FGA was test by using Rank Spearman.   The results of this research show that the role of FAI shows with the score of 39.27 and the development of FGA with the score of 36.79. The results of data analysis show χ2count of 8.06 and χ2table (α = 0.05) of 3.84 also tcount of  3.92 and ttable (α = 0,05) of 1.68 so that can be concluded that there is a close relationship between the role of FAI and the development of FGA in Wonosari Village, Sepaku Subdistrict, Penajam Paser Utara District.